PROFESIONALISME MILITER DI KOREM 032 WIRABRAJA SUMATERA BARAT - Tiara, Inoki Ulma (TINGKAP, 2013)
Together with national reformation, Indonesian national military has been realized with the need of doing professionalism. Professionalism inside of national army has become consciousness and commitment of Angkatan Bersenjata Republik Indonesia (ABRI), especially Indonesian army ground forces (TNI AD). TNI as organization which defense the country is hoped more advance and modern. In democration country, the duty of TNI and the army has been described clearly, that is old professionalism which is only at defense aspect. This research is for understanding of TNI professionalism in Korem 032 Wirabraja West Sumatera. Based on data analysis, it shows that the response to the military professionalism inside of TNI is very good. The effect of response of professionalism of military inside of TNI AD at Korem 032 Wirabraja West Sumatera has been occured directly that make professional aspect clearly. The duty of TNI AD at Korem 032 Wirabraja is only on defense aspect. Keywords: Democracy, military, defense, professionalism